1995
DOI: 10.1161/01.cir.91.5.1403
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Serum Lipoprotein(a) Is a Risk Factor for Clinical Recurrence After Coronary Balloon Angioplasty

Abstract: An elevated Lp(a) concentration was a risk factor for clinical recurrence after percutaneous transluminal balloon coronary angioplasty. Other lipid levels or clinical characteristics were not significantly associated with recurrence. When serum was frozen and stored for a prolonged period, Lp(a) concentration decreased over time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
0
3

Year Published

1997
1997
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 116 publications
(43 citation statements)
references
References 45 publications
0
40
0
3
Order By: Relevance
“…Most of the previously published studies addressing the issue had methodological defects or constraints limiting the usefulness of the results. Various limitations of these studies included retrospective analysis 10,16 ; small sample size 9,11,14,15,18 ; inclusion of patients and measurement of Lp(a) within 4 weeks of acute myocardial infarction, 10,12 which increases Lp(a) for at least 4 weeks 21,23 ; blood sampling after PTCA 9,10,12,16 ; the interventional nature of the study 17 ; or assay of stored samples, 13 which can yield artifactually low levels of Lp(a).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the previously published studies addressing the issue had methodological defects or constraints limiting the usefulness of the results. Various limitations of these studies included retrospective analysis 10,16 ; small sample size 9,11,14,15,18 ; inclusion of patients and measurement of Lp(a) within 4 weeks of acute myocardial infarction, 10,12 which increases Lp(a) for at least 4 weeks 21,23 ; blood sampling after PTCA 9,10,12,16 ; the interventional nature of the study 17 ; or assay of stored samples, 13 which can yield artifactually low levels of Lp(a).…”
Section: Discussionmentioning
confidence: 99%
“…The only study of comparable size to ours that showed a significant relation of Lp(a) level to risk of restenosis measured the Lp(a) level 4 weeks after angioplasty in 93 subjects who had a history of myocardial infarction within 1 month of PTCA from a total cohort of 240 subjects. 12 These Lp(a) measurements after PTCA may have confounded the analysis of Lp(a) as a predictor of risk for restenosis. Another study of comparable size, which has been reported in abstract form, found no significant correlation of Lp(a) with restenosis but was designed to test the effect of lipid lowering on restenosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8] Percutaneous transluminal coronary angioplasty (PTCA) with or without stent implantation is an established revascularization procedure; however, restenosis rates still range between 30-60% 6 and 15-30%, 7 respectively Preprocedural identification of low-and high-risk patients who might benefit from additional procedures 6,8 would be desirable. However, the predictors of early [7][8][9][10] and late complications [11][12][13][14][15] have a low predictive value, [15][16][17][18] are available only after procedures, 9,14 or are not easily applicable in clinical practice. 10,12,13 Inconsistent and weak correlation with early complications following PTCA was reported for female gender, extreme age, diabetes, multivessel disease, lesion characteristics, and hemostatic variables.…”
Section: Introductionmentioning
confidence: 99%
“…10,12,13 Inconsistent and weak correlation with early complications following PTCA was reported for female gender, extreme age, diabetes, multivessel disease, lesion characteristics, and hemostatic variables. [6][7][8][9][10][11][12][13][14][15][16][17][18] This study was therefore undertaken to investigate the short-and long-term prognostic value of preprocedural serum levels of CRP in patients with AMI receiving PTCA/stenting.…”
Section: Introductionmentioning
confidence: 99%